Efficacy of new beverage made of dates vinegar and garlic juice in improving serum lipid profile parameters and inflammatory biomarkers of mildly hyperlipidemic adults: A double‐blinded, randomized, placebo‐controlled study. Issue 5 (2nd April 2018) - Ali, Zeshan; Ma, Haile; Ayim, Ishmael; Wali, Asif
Abstract: A beverage made from date vinegar and garlic juice was recently developed for use by people who wish to attain maximum quantities of both vinegar and polyphenols for their health and do not like to use vinegar and garlic directly in their daily diet. Fifty hyperlipidemic adults consumed two cups (500 mL) of either the new beverage or a placebo daily over a period of 7 weeks. Plasma lipids, inflammatory biomarkers, urea, creatinine, potassium, and β‐carotenoid concentrations were measured before and after each treatment. A recommended dose of 500 mL of the new beverage reduced total cholesterol (TC) (260.10 ± 17.9 to 198.90 ± 17.31 mg/dL) and C‐reactive protein (CRP) (8.04 ± 1.34 to 4.45 ± 1.42 mg/L) along with heart rate and mean blood pressure. These outcomes indicate that the new beverage improved the concentration of lipids and inflammatory biomarkers, and the new beverage is beneficial for people who are worried about hypertension. Practical applications: Dietary therapy is the primary step in the treatment of hyperlipidemia. Dates, compared with different fruits, are a rich source of phenolic compounds. Researchers have claimed that extract of date fruit is effective in improving lipid profile parameters. Similarly, evidence from other studies has indicated that garlic can bring about the regulation of blood cholesterol along with the improvement of fibrinolytic activity and decrement of blood pressure. Thus, this study will provide a possible source of phenolic compounds and present a latent approach to the avoidance of hyperlipidemia and hypertension. This new beverage is suggested as a dietary supplement for the promotion of a healthy heart.